Anmerkung zu EuGH, Urt. v. 7.11.2019 - C-349/18 bis C-351/18, Kanyeba - Rodi, Daniel (GPR, 2020)
The C.J.E.U. decided, that Article 3(8) of Regulation (EC) No 1371/2007 must be interpreted as meaning that a situation in which a passenger boards a freely accessible train for the purposes of travel without acquiring a ticket comes within the concept of a ‘transport contract’ for the purposes of that provision. On this occasion the C.J.E.U. also stated, that the word ‘contract’ is generally understood to designate an agreement by consensus intended to produce legal effects.
Gesehen am 04.11.2020